Clinical efficacy of antiangiogenic therapy for diabetic macular edema in real clinical practice (2-year results) - A. Zh. Fursova; A. S. Derbeneva; M. S. Tarasov; M. V. Vasil’eva; J. A. Gamza; N. V. Chubar (Российский офтальмологический журнал)
Purpose:to evaluate the clinical efficacy of anti-VEGF therapy of patients with diabetic macular edema (DMO) in T & E regimen for 96 weeks. Materials and methods. The study included 59 patients (101 eyes) with DMO. The average number of intravitreal injections of anti-VEGF agent (IIAVA) — aflibercept given during the whole period was 12.87 ± 3.56, including 7.78 ± 1.20 in the first year, and 4.82 ± 2.66 in the second year. Results.All patients showed an increase in visual functions (+0.33, p < 0.001) with a maximum achieved after 5 injections (+0.24; p = 0.001). Central macular thickness decreased from 397.36 ± 100,00 μm at the initial level to 276.59 ± 52.90 after 5 loading injections (-120.8 μm), to 263.85 ± 45.20 (-133, 91 μm) after 1 year and to 248.6 ± 46.9 (-148.76 μm) after 2 years. A resorption of retinal neuroepithelial detachment was observed in 84.16 % of cases as soon as loading injections were given, and reached 100 % of cases by the 48th week of observation. Strong inverse correlations were revealed between the initial presence of medium and large intraretinal cysts and visual acuity, both initial and final (-0.35 and -0.42, p < 0.01). The disorganization of retina inner layers at the initial level was a predictor of a worse visual outcome at the end of the observation period. By the end of this period, 44 patients (43.5 %) received IIAVA with an interval of 12 weeks, the maximum interval between injections was 16 weeks and was achieved in 19 (28.01 %) eyes. Conclusion.The results of a 2-year retrospective study of the efficacy of aflibercept in DME showed that T&E regimen can be used with highfunctional results. Due to flexible planning of the number of IIAVA in the second year, over-treatment could be avoided without reducing the expected efficacy.